The effect of live streaming on purchase intention of e-commerce customers - Sarah Sarah; Nurdin Sobari (President University, 2022)
Live streaming is one of many features that e-commerce offers to help sellers showcase products in real-time through live video. During the pandemic Covid-19, live streaming became popular and grew as an important selling tool for sellers in e-commerce. Drawing from previous literature adoption behavior and social commerce, this paper proposes a framework that examines purchase intention on live streaming and its relationship with customer trust and engagement. A conceptual model including thirteen hypotheses was developed and tested on 207 valid questionnaires. The result indicates that hedonic and symbolic value in live streaming positively affects trust in products, while utilitarian and hedonic significantly affect trust in sellers. In the e-commerce context of live streaming, only hedonic and symbolic values positively impact customer engagement and trust in products. Finally, customer engagement in live streaming significantly affected purchase intention. Implications for theoretical and managerial are further discussed at the conclusion of this paper.